LEGAL CONSEQUENCES ON COMPLETE SYSTEMATIC LAND REGISTRATION RELATED TO BPHTB DEBT (World Bulletin of Management and Law, 2023)
Issuance of certificates from the PTSL program is still given even though BPHTB payments have not been made. Problems will arise again if the owner of the certificate will transfer his rights, he is required to pay the tax owed complete with the obligation to pay fines/sanctions. This is considered a burdensome for the community, because there is no clear socialization. While people who sell or transfer their rights are those who have urgent needs so they sell their assets, at the same time they also have to pay a large amount of tax. The purpose of this research is to find out and analyze the legal consequences of a complete systematic land registration related to the fees for obtaining land rights and buildings that are owed.